2004
DOI: 10.1142/s0218396x04002080
|View full text |Cite
|
Sign up to set email alerts
|

A Fem-Based Quasi-Static Neuro-Model for Acoustic Noise in Switch Reluctance Motors

Abstract: Elimination of stator oscillations in electromotors is among the least studied, but important problems that can influence the electric performance, mechanical wear and tear and acoustical noise. In this paper, we focus on a switch reluctance motor (SRM) designed and prototyped for eventual production in Iran. The stator oscillation problems due to radial forces in SRMs have been reported as more acute as compared to similar motors. Due to the complicated mechanical and electrical structure of SRMs, obtaining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, when Lucas et al attempted to predict high-frequency aerodynamic noise using the FEM, satisfactory results were unavailable. ey indicated that the FEM could not predict high-frequency noise; that is, as the frequency increased, the modes of the structure became denser and could not be identified by the current identification technologies [27]. erefore, the FEM was primarily used to predict the structural and wheel-rail noise of the car body.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, when Lucas et al attempted to predict high-frequency aerodynamic noise using the FEM, satisfactory results were unavailable. ey indicated that the FEM could not predict high-frequency noise; that is, as the frequency increased, the modes of the structure became denser and could not be identified by the current identification technologies [27]. erefore, the FEM was primarily used to predict the structural and wheel-rail noise of the car body.…”
Section: Literature Reviewmentioning
confidence: 99%